Alteration of transporter activities in the epididymides of infertile initial segment-specific Pten knockout mice() - Xu, Bingfang (Biol Reprod, 2018)
A fully functional initial segment, the most proximal region of the epididymis, is important for male fertility. Our previous study generated a mouse model to investigate the importance of initial segment function in male fertility. In that model, phosphatase and tensin homolog (Pten) was conditionally removed from the initial segment epithelium, which resulted in epithelial de-differentiation. When spermatozoa progressed through the de-differentiated epithelial duct, they developed angled flagella, suggesting compromised sperm maturation, which eventually resulted in male infertility. To understand the molecular mechanisms, by which PTEN regulates epididymal sperm maturation, we compared the transcriptome profile of the initial segment between controls and initial segment-specific Pten knockouts and revealed that water, ion, and organic solute transporter activities were one of the top molecular and cellular functions altered following loss of Pten. Alteration in protein levels and localization of several transporters following loss of Pten were also observed by immunofluorescence analysis. Epithelial cells of the initial segment from knockouts were more permeable to fluorescein isothiocyanate–dextran (4000 Da) compared to controls. Interestingly, conditional deletion of Pten from other organs also resulted in changes in transporter activity, suggesting a common role of PTEN in regulation of transporter activity. Taken together, our data support the hypothesis that loss of Pten from the initial segment epithelium results in changes in the transporting and permeability characteristics of the epithelium, which in turn altered the luminal fluid microenvironment that is so important for sperm maturation and male fertility.